Penelusuran Potensi Kapulaga, Temu Putri dan Senggugu sebagai Penghambat Pembentukan Biofilm - TRIANA HERTIANI; SINTAYU PUTRI WANDAN SARI; FERRY RAHMA PUSPITA; NURI IRIYANI; SYLVIA UTAMI TUNJUNG PRATIWI (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Kapulaga fruit, temu putri rhizome and sengugu bark have been reported as antibacterials, suggesting potency to be developed as antibiofilm agents. This research has investigated the inhibition activity on biofilm formation of Methicillin-resistant Staphylococcus aureus (MRSA) and Escherichia coli. Following petroleum ether extraction, the remaining biomass was macerated in ethanol 70 %. After solvent evaporation, the ethanol extract was partitioned to yield hexane, ethyl acetate and water fractions. The inhibition activities of ethanol extracts, hexane, ethyl acetate and water fractions of samples were carried out in vitro on microplates flexible U-bottom 96 wells using crystal violet staining and were recorded at λ 595nm. Phytochemical identification were performed by thin layer chromatography. Results showed that extract or fraction samples which have the highest biofilm inhibition activity toward MRSA were hexane fraction of kapulaga IC50 0.23±0.01 mg/mL, temu putri IC50 0.45±0.03 mg/mL and the ethyl acetate fraction of senggugu IC50 0.35±0.022 mg/mL. Biofilm inhibition activity toward E. coli, were shown by the ethyl acetate fractions of kapulaga IC50 0.32±0.17 mg/mL, temu putri IC50 0.46±0.03 mg/mL and senggugu IC50 0.39±0.02 mg/mL.